Research on Features of the Product Development Process I n Supply Chain Management in Russia: Assessment, Trends, and Prospects - Bogomolova Irina Petrovna; Krivenko Elena Ivanovna; Trineeva Lyudmila Timofeevna; Ustyugova Irina Evgenievna; Vorontsova Julia Nikolaevna (International Journal of Supply Chain Management, 2020)
Abstract— Designing products to match the processes and supply chains, processes to match product platforms and supply chains, and supply chains to match the product platforms and process are they ingredients in today's fast developing markets. In the course of the study the following results were achieved: assessment of trends in the development of wine production from the supply chain management retrospective at the national and international levels was done. Market of grape wine, wine products, as well as champagnes and sparkling wines in the Russian Federation were studied through the supply chain management for wine production process from supplier to costumer. The structure of the wine sales in Russia by types was evaluated and positive and negative tendencies in development of modern Russian winemaking were formed. Results showed that supply chain system in wine industry of Russia can overcome the difficulties of import and export in this country. In conclusion, a specific list of measures that need to be implemented at the state level to ensure a sustainable trend in the development of the domestic wine industry was defined.